Vital Pulp Therapy with Calcium-Silicate Cements: Report of Two Cases - Ashraf, Hengameh; Rahmati, Afsaneh; Amini, Neda (Iranian Endodontic Journal, 2016)
This article describes successful use of calcium-enriched mixture (CEM) cement and Biodentine in apexogenesis treatment in two 8-year-old patients, one with immature permanent molar diagnosed primarily with irreversible pulpitis and the other with partially vital maxillary central incisor. After access cavity preparation, partial pulpotomy in molar and full pulpotomy in central was performed, and the remaining pulps was capped with either Biodentine or CEM cement, in each tooth. The crowns were restored with composite filling material at the following visit. The post-operative radiographic and clinical examinations (approx. average of 16 months) showed that both treated teeth remained functional, with complete root development and apex formation. A calcified bridge was produced underneath the capping material. No further endodontic intervention was necessary. Considering the healing potential of immature vital pulps, the use of CEM cement and Biodentine for apexogenesis might be an applicable choice. These new endodontic biomaterials might be appropriate for vital pulp therapies in an immature tooth. However, further clinical studies with longer follow-up periods are recommended. Keywords:Apexogenesis; Calcium-Silicate Cements; Dental Pulp; Pulpotomy; Vital Pulp Therapy